Developing a Graded Examination for the Malay Gamelan - Shah, Shahanum Mohamad; Saidon, Zaharul Lailiddin (Malaysian Journal of Music, 2017)
The traditional music of Malaysia appears to be sidelined in favour of music which is more accessible and readily available to the younger generation. The lack of exposure to traditional music breeds unfamiliarity of this music and hence is not appreciated or understood by most Malaysians. As music is an integral part of human culture, it is important for this genre of music to be sustained for the future generation. As compared to the availability of examination systems for Western music, there are no mechanisms for assessing musical attainment for the local music traditions in Malaysia. A structured system for assessing and awarding certificates based on levels of achievement in the local music traditions is needed which will provide a platform for musicians involved in the local music traditions to benchmark their achievements and obtain the necessary qualifications which can assist them in furthering their studies or gain employment. This paper discusses the development of a graded examination system for the Malay gamelan in an effort to sustain this tradition. This study used the qualitative method whereby both desk work and field work are conducted. Research methods used include observation of performances, being a participant-observer during practices, interview sessions and focus groups with various practitioners from Malaysia and Indonesia and audio/visual documentation. Guidelines on developing a graded examination system for the Malay gamelan are discussed.